2000
DOI: 10.1017/s0950268800003605
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of the emergence of vaccine-resistant hepatitis B in The Gambia using a mathematical model

Abstract: SUMMARYVaccine escape variants of hepatitis B virus (HBV) have been identified world-wide. A mathematical model of HBV transmission is used to investigate the potential pattern of emergence of such variants. Attention is focused on The Gambia as a country with high quality epidemiological data, universal infant immunization and in which escape mutants after childhood infections have been observed. We predict that a variant cannot become dominant for at least 20 years from the start of vaccination, even when us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Variants in the dominant population, defined as variants replacing the wild-type strain in the major viral population, may be acquired at the onset of HBV infection. This concept is supported by the results of previous studies, which have shown that the replacement of the wild-type strain with a variant may take Ͼ50 years (64)(65)(66). Some immune escape variants were identified in the dominant population, which indicates that these variants are relatively stable in the absence of the wild-type strain.…”
Section: Discussionsupporting
confidence: 66%
“…Variants in the dominant population, defined as variants replacing the wild-type strain in the major viral population, may be acquired at the onset of HBV infection. This concept is supported by the results of previous studies, which have shown that the replacement of the wild-type strain with a variant may take Ͼ50 years (64)(65)(66). Some immune escape variants were identified in the dominant population, which indicates that these variants are relatively stable in the absence of the wild-type strain.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have suggested that such variants are more common in patients with long-standing or more advanced HBV infections, but others have not confirmed these findings [15][16][17][18][19]. That S-variants were significantly more common in the older age groups of Groups 1 and 2 subjects would be in keeping with the former findings.…”
Section: Discussionmentioning
confidence: 79%
“…However, the level of HBV prevalence identified from our study would remain consistent with values of R 0 <3. In addition, an analysis based on a fully age-structured mathematical model of HBV transmission in The Gambia [15] gave an estimate of R 0 y2 for this high endemicity country.…”
Section: Discussionmentioning
confidence: 99%
“…Such data help in the development of appropriate control measures, for example, estimating the optimal age for vaccine delivery, the level of vaccine coverage required for elimination, and possible high-risk target groups [10,11]. They support predictive mathematical models by which to explore the merits of different control options [11][12][13], to assess cost-effectiveness of intervention programmes [14], and to predict the risk of evolution of escape mutants [15].…”
Section: Introductionmentioning
confidence: 99%